Pembuatan Pakan Ikan Pada Kelompok Budidaya Ikan di Ungaran Untuk Mengurangi Biaya Produksi - Deri Herdawan; Sri Tutie Rahayu; Susanto Susanto; Widar Bayu Wantoro; Noviarianto Noviarianto; Arif Rakhman Suharso; Wahyu Ari Putranto; Nur Kholis (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This community service program is carried out in Beji Village, East Ungaran District, which is around the Indonesian State Maritime Polytechnic campus. This activity is a continuation of the previous service roadmap in the same place where in the previous service activity, making fish food using a pellet molding machine using a petrol motor, this time making fish food using a manual fish pellet molding machine. The aim is to introduce MSME service partners to the fish cultivation group in Beji sub-district about the types of fish pellet molding machines so that they can meet fish feed needs to save production costs. The method for implementing this activity is by providing training by sharing knowledge about the parts of the fish pellet molding machine and the composition of the ingredients that make up good fish feed, followed by the practice of making fish feed using a manual pellet molding machine.